2020
DOI: 10.1186/s12958-020-00595-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between the quality of inner cell mass and first trimester miscarriage after single blastocyst transfer

Abstract: Background: The blastocyst morphology provided valuable roles for predicting pregnancy and live birth, but was still not fully understood for evaluating miscarriage. The aim of this study was to explore the association between blastocyst morphologic evaluation and first trimester miscarriage combined with karyotype of miscarried conceptus. Methods: This retrospective cohort study included a total of 2873 clinical pregnancy cycles with single blastocyst transfer performed from January 2013 to April 2019. Chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…In the present study, we found that Group B and FET cycles with Day 6 blastocysts had a significantly higher rate of CPL than Group A and FET cycles with Day 5 blastocysts, respectively. Part of these results was consistent with previous reports that transfer of Day 6 blastocysts resulted in a significantly higher miscarriage rate than that of Day 5 blastocysts (43,44). These results indicated that MA or days of blastocyst could serve as an independent factor affecting the occurrence of CPL.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, we found that Group B and FET cycles with Day 6 blastocysts had a significantly higher rate of CPL than Group A and FET cycles with Day 5 blastocysts, respectively. Part of these results was consistent with previous reports that transfer of Day 6 blastocysts resulted in a significantly higher miscarriage rate than that of Day 5 blastocysts (43,44). These results indicated that MA or days of blastocyst could serve as an independent factor affecting the occurrence of CPL.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study reported no statistical correlation between miscarriage and the grade of ICM or TE (43). In that study, they only included blastocysts with grade A or B ICM and without grade C ICM; therefore, it is not strange that no association of ICM grade with miscarriage was observed (43). However, that study showed a trend that the C score of TE was related to a higher rate of miscarriage (43).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…As expected, we showed that number of embryos transferred positively while female age adversely affected clinical pregnancy and live birth, indicating the con dence of our data. In line with a recent study (34), transfer of day 6 blastocysts increase the risk of abortion than transfer of day 5 blastocysts. After controlling factors including female or male age, number of embryos transferred, female BMI, semen DFI and days of blastocyst, we found MG blastocysts from the L group showed decreased chance of implantation or live birth, compared to MG blastocysts from the H group.…”
Section: Discussionsupporting
confidence: 88%